Creating urban spaces and medium-sized cities - Biloshytska, Nataliia; Tatarchenko, Halyna; Biloshytskyi, Mykola; Tatarchenko, Zakhar (Academic journal Industrial Machine Building Civil Engineering, 2020)
The research relevance is determined by the need to draw up a specific reference, regulatory and procedural documents that take into account regional features in designing public spaces. The analysis of urban spaces is carried out based on the example of the city of Severodonetsk to identify the spatial planning pattern of these elements and issues of their creation. It is found out that the main problem in creating public spaces is uncertainty in the regulations on urban development, namely, their number in the city, functionality, spatial planning pattern, design. There is revealed the unstructuredness of some elements of public spaces; lack of clear ranking and functional zoning in some cases; detachment of urban public spaces from the natural landscape.